Corn Farmer Income Analysis in the Penengahan District of South Lampung Regency - Maya Riantini; Ktut Murniati; Yunita Munisara (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2021)
Corn is one of the crops that, after rice, provides the second most carbs. Corn is utilized for livestock and the processed food sector in addition to food. The purpose of this study is to look at the income of maize producers in Penengahan District, South Lampung Regency's. At the locations of Sukabaru Village and Kelaten Village, Penengahan District, South Lampung Regency, this study used a survey method with a direct interview using questionnaires. A basic random sampling strategy was used in this study, which included 51 corn producers. The average household income of maize farmers in Penengahan District is IDR 40692322,08 per year, according to the findings. Corn farmers' household income in accumulation from corn on farm income was IDR 32634674,96 per year, off farm income was IDR 5872941,24 per year, and non farm income was IDR 2396470,44 per year.